RESONANT ELECTROMAGNETIC PROCESSES AT UNSTABLE OPERATION OF SLIDING CURRENT COLLECTOR UNITS OF TURBOGENERATOR (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The article is devoted to study of the resonance electromagnetic oscillations arising during unstable operation of the sliding current collection unit of turbo-generators. Mathematical modeling of these processes is carried out. It has been established that it is these processes that are the main cause of increased sparking and “ring fire” or “breakdown of commutation” on contact rings.